2016
DOI: 10.5146/tjpath.2015.01344
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of aldh1, ezh2 and ki-67 in astrocytic gliomas

Abstract: Objective: tumor stem cells have been found in a variety of neoplasms and stated to have a role in tumor progression. This study aimed to evaluate the prognostic significance of biomarkers which are said to be related to these cells, i.e., EZH2, ALDH1 and Ki-67, and their correlation with each other in astrocytic gliomas. Material and Method:Formalin-fixed, paraffin-embedded tissue specimens of 40 patients with astrocytic glioma who underwent initial surgery during the period from December 2011 to May 2014 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Two studies [15, 17] were conducted in China, one [16] was performed in Canada, one [18] was in Egypt, one [19] was in India and one [20] was in Germany, respectively. Four studies [15, 16, 18, 19] examined EZH2 expression by immunohistochemistry staining (IHC) and two [17, 20] used genetic testing. All six studies investigated the prognostic value of EZH2 for OS and three studies [16, 18, 19] explored the association between EZH2 and PFS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies [15, 17] were conducted in China, one [16] was performed in Canada, one [18] was in Egypt, one [19] was in India and one [20] was in Germany, respectively. Four studies [15, 16, 18, 19] examined EZH2 expression by immunohistochemistry staining (IHC) and two [17, 20] used genetic testing. All six studies investigated the prognostic value of EZH2 for OS and three studies [16, 18, 19] explored the association between EZH2 and PFS.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [15, 16, 18, 19] examined EZH2 expression by immunohistochemistry staining (IHC) and two [17, 20] used genetic testing. All six studies investigated the prognostic value of EZH2 for OS and three studies [16, 18, 19] explored the association between EZH2 and PFS. The detailed characteristics of included studies were depicted in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki-67/MIB-1 is the most widely used marker for assessing the proliferative capacity of tumor cells. Increased expression of Ki-67/MIB-1 has been linked to increased invasiveness in many cancers 10,6567. Many meta-analyses have shown that high expression of Ki-67/MIB-1 contributed to poor survival in many tumors 6872.…”
Section: Discussionmentioning
confidence: 99%
“…Together with IDH1 gene mutation, MGMT protein expression level and Ki67 index were identified as independent prognostic factors for PFS in multivariate Cox regression analysis. The value of Ki67 and MGMT as independent prognostic factors in glioma was reported previously 5155 . We classified 47 astrocytic tumours into 3 groups based on IDH1 mutation status and MGMT and Ki67 expression level without considering histological grade.…”
Section: Discussionmentioning
confidence: 57%